(untitled) (Malay Literature, 2018)
This qualitative study was intended to document and perceive the existing narratives on the origins of mantra among the Bajau community living in the villages of Kampung Mapan-Mapan Darat and Kampung Mapan-Mapan Laut in Pitas, Sabah. This study uses participant observation as a systematic method of collecting data on mantra through three informants, who are also experienced mantra practitioners, residing in the two said villages. The data collected was analyzed using Malinowski’s functional theory, which emphasizes on analyzing the origins of occurrences and cultural phenomena in an ethnic group. This study focused more on the Bajau community’s need for safety and food. The urgent documentation of the narrative of mantra is imperative before the practice disappears from the cultural expressions of the Bajau community. Keywords: narrative, origins, mantra, Bajau community